2015
DOI: 10.1093/gerona/glv029
|View full text |Cite
|
Sign up to set email alerts
|

The Virtual Short Physical Performance Battery

Abstract: In spite of the similarity between the SPPB and vSPPB, the moderate strength of the association between the two suggests that they offer unique perspectives on an older adult's physical function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 33 publications
1
28
1
Order By: Relevance
“…The SPPB could be adopted for characterizing physical function as well as documenting changes over time. Researchers and clinicians might consider using a recent virtual SPPB for ongoing measurement of physical function in older adults with MS [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The SPPB could be adopted for characterizing physical function as well as documenting changes over time. Researchers and clinicians might consider using a recent virtual SPPB for ongoing measurement of physical function in older adults with MS [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that walking speed alone can represent nearly all of the predictive value of the SPPB [31], is quick and low cost, and may be done outside of a clinical setting. There has also been some work to validate self-reported performance on tests of physical performance, using a “virtual SPPB” test [32]. It would be feasible to design an app that participants downloaded and allowed them to test their walking speed with automatic notification to the study team as to whether they were eligible or not.…”
Section: Discussionmentioning
confidence: 99%
“…Participants will be eligible for the PA module based on health conditions identified in the Australian National University Alzheimer’s Disease Risk Index Short Form (ANU-ADRI-SF [18, 19], medical history (MYB Medical History), and MYB Physical Assessment battery (includes measures of body composition, Harvard Alumni Questionnaire [20], International Physical Activity Questionnaire [21] sitting, and Virtual Short Physical Performance Battery Protocol [22]). Risks identified include low levels of physical activity (aerobic and/or resistance training), high levels of sitting, high blood pressure, dyslipidemia, diabetes, heart related issues, stroke, transient ischemic attack (TIA), high body mass index (BMI), high waist circumference, and active smoking status.…”
Section: Methodsmentioning
confidence: 99%
“…The PA module will be adjusted if a participant reports being diagnosed with osteoporosis, or a high number of falls in the past 12 months, or scores poorly in the virtual Short Physical Performance Battery (vSPPB) [22] by removing any goals and feedback related to aerobic exercise as walking may increase risk of falls until strength and balance are improved [34, 35]. During annual assessments, participants could be reallocated to the main PA module if appropriate.…”
Section: Methodsmentioning
confidence: 99%